How to measure the oxidation state of multivalent elements in minerals, glasses, and melts? - Neuville, Daniel R.; Cicconi, Maria Rita; Losq, Charles Le (Wiley Blackwell, 2021)
All natural materials and most manufactured technologically relevant materials contain a variable but consequent amount of multivalent elements, like iron. Many physicochemical properties of materials highly depend on the type of multivalent cations they contain, as well as on the concentrations and redox states of those multivalent elements. For instance, color is probably the most visible characteristic, resulting from the presence of multivalent transition elements. Other properties like viscosity and density of liquids are affected by those elements, and, as such, they can be seen as important variables for geologic and industrial phenomena. The present contribution focuses on providing an overview of the most common techniques currently in use for the investigation of multivalent elements in natural and industrial materials. It covers both destructive and non-destructive methods, as well as element-specific and bulk techniques.
CRIS-Team Scopus Importer:2024-12-16
Keywords: Electronic microprobe; In situ redox determination athigh temperature or at high pressure; Mössbauer spectroscopy; Optical absorption spectroscopy; Raman spectroscopy; Wet-chemical analyses; X-ray absorption spectroscopy